Income and Efficiency Analysis of Maize Farming in Pringgabaya District East Lombok Regency - Aeko Fria Utama FR; Dudi Septiadi; Muhammad Nursan (Jurnal Biologi Tropis, 2022)
East Lombok Regency is one of the maize development areas in NTB Province, however, maize productivity in that area is still relatively low due to the inefficient use of production inputs.The aims of this research are to; 1) analyze the income of corn farming in Pringgabaya District, East Lombok Regency; 2) analyze the factors that influence corn production in Pringgabaya District, East Lombok Regency; 3) analyze the level of economic efficiency in the use of production factors in corn farming in Pringgabaya District, East Lombok Regency. The research method used is descriptive method with a quantitative approach. The location of the research was carried out in Bagek Papan Village and Pringgabaya Village, Pringgabaya District, East Lombok Regency. Respondents in this study were farmers who cultivate corn in paddy fields as many as 30 respondent farmers. Data collection techniques used in this study are survey and interview techniques. Analysis of the data used in corn farming is farm income analysis, Cobb-Douglass production function analysis and efficiency analysis of production factors. The results showed that the income of farmers obtained from corn farming in Pringgabaya District, East Lombok Regency in 2021 was IDR 11,671,745 per arable area or IDR 15,559,705 per hectare. The factors that affect production that have a significant (significant) effect on production are land area at a significant level of 5% and NPK fertilizer at a significant level of 10%. Meanwhile, other variables, namely labor, seeds, urea, TSP and pesticides had no significant effect at the 5% and 10% levels. The production factors used in corn farming in Pringgabaya District, East Lombok Regency are not and have not been efficient to cultivate, this can be seen from the efficiency criteria that have not and none have achieved efficiency with a value of NPMx/Px = 1.